Response of Coppicing Albizia lebbek at Different Heights on Regeneration and Subsequent Biomass Production - Saleem, M.; Singh, D. P. (Indian Forester, 1995)
Effect of coppicing at different heights on regeneration and subsequent biomass production of Albizia lebbek was studied using randomized block design with 10 trees per block and three replications. Seven pruning heights applied were 5 cm (ground level), 15 cm, 30 em, 45 em, 60 cm, 75 cm and 90 em. Investigations showed that 90 cm coppicing height resulted in increased biomass productions compared to coppicing at ground level. Results can be used for maximizing biomass production when managed as multi-stemmed shrub in agroforestry systems.